Microsoft Office Home and Student Edition 2013 All-in-One For Dummies - Weverka, Peter (Hoboken, New Jersey John Wiley & Sons, Inc., 2013)
The Home & Student version of Microsoft Office targets the home and education markets, covering the four applications most used outside the workplace: Word, Excel, PowerPoint, and OneNote. The minibooks in this essential All-in-One guide include real-world examples and projects that cover the new features and capabilities of Office 2013. Straightforward advice and beneficial projects help you to learn the basics of creating a resume in Word, establishing a home budget in Excel, developing a dynamic school presentation with PowerPoint, and taking notes in OneNote.
Includes Index and Illustrations.
Keywords: Microsoft Office